Synergistic Radiosensitization Mediated by Chemodynamic Therapy via a Novel Biodegradable Peroxidases Mimicking Nanohybrid - Zhang, Jun; Jiang, Dazhen; Lyu, Meng; Ren, Shiqi; Zhou, Yunfeng; Cao, Zhen (Frontiers in Oncology, 2022)
Purpose: During radiotherapy, the amount of reactive oxygen species (ROS) is inadequate for suppressing cancer cell. Herein, we designed a biodegradable mesoporous silica decorated with hemin and glucose oxidase (GOD@Hemin-MSN) for chemodynamic therapy to enhance radiotherapy. Methods: Mesoporous silica as an outstanding drug carrier can deliver hemin and glucose oxidase to tumor site. Cancer cells with high level of metabolism activity, is abundant in glucose which can be oxidized into H2O2 by glucose oxidase (GOD). Next, generated H2O2 was then converted to intracellular reactive oxygen species (ROS), especially hydroxyl radical within tumor tissues, by hemin with peroxidase mimetic property. Thus, the deficient ROS could be made up via this process. Results: This chemodynamic therapy induced by GOD@Hemin-MSN produce quantities of ROS, which composited for the inadequate ROS resulting from radiotherapy, and exhibited remarkable antitumor efficacy with tumor inhibition rate of 91.5 % on A549-tumor bearing mice. Conclusion: This work has validated GOD@Hemin-MSN as a radiosensitizer by chemodynamic therapy with biocompatibility, as well as potential for translational application.